2021
DOI: 10.1021/acs.iecr.0c04375
|View full text |Cite
|
Sign up to set email alerts
|

Improving Ti Incorporation into the BEA Framework by Employing Ethoxylated Chlorotitanate as Ti Precursor: Postsynthesis, Characterization, and Incorporation Mechanism

Abstract: The liquid–solid postsynthetic method is commonly used in the preparation of metal-containing zeolites, for example, Ti-β (BEA) zeolite. This paper reports a facile and Ti incorporation improved liquid–solid impregnation method for Ti-β zeolite preparation by incorporating a unique Ti precursor, namely, partially ethoxylated chlorotitanate (Ti­(Cl)4–n (OEt) n ), into the defects of dealuminated β zeolite. The Ti precursor was prepared from the reaction of TiCl4 and ethanol, and its structure was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…The isolated tetrahedral heteroatom metal species in the framework are generally believed to be more active than those in the extra-framework. 24,93 The location of heteroatom metals in zeolites can be determined by X-ray diffraction (XRD), Raman spectroscopy, diffuse reflectance ultravioletvisible (UV-vis) spectroscopy, X-ray photoelectron spectroscopy (XPS) and X-ray absorption near-edge spectroscopy (XANES).…”
Section: Determination Of the Location Structure And Acidity Of Heter...mentioning
confidence: 99%
“…The isolated tetrahedral heteroatom metal species in the framework are generally believed to be more active than those in the extra-framework. 24,93 The location of heteroatom metals in zeolites can be determined by X-ray diffraction (XRD), Raman spectroscopy, diffuse reflectance ultravioletvisible (UV-vis) spectroscopy, X-ray photoelectron spectroscopy (XPS) and X-ray absorption near-edge spectroscopy (XANES).…”
Section: Determination Of the Location Structure And Acidity Of Heter...mentioning
confidence: 99%
“…Liang et al reported a facile and Ti incorporation improved liquid-solid impregnation method for Ti-β zeolite preparation by incorporating a unique Ti precursor. Among the other characterization techniques, EGA-MS allowed defining of the function mechanism of this unique Ti precursor [ 192 ].…”
Section: Applications To Zeolitesmentioning
confidence: 99%